Is the nuclear refractive index lower than cytoplasm? Validation of phase measurements and implications for light scattering technologies. Issue 12 (18th April 2017) - Steelman, Zachary A.; Eldridge, Will J.; Weintraub, Jacob B.; Wax, Adam
Abstract: The refractive index (RI) of biological materials is a fundamental parameter for the optical characterization of living systems. Numerous light scattering technologies are grounded in a quantitative knowledge of the refractive index at cellular and subcellular scales. Recent work in quantitative phase microscopy (QPM) has called into question the widely held assumption that the index of the cell nucleus is greater than that of the cytoplasm, a result which disagrees with much of the current literature. In this work, we critically examine the measurement of the nuclear and whole‐cell refractive index using QPM, validating that nuclear refractive index is lower than that of cytoplasm in four diverse cell lines and their corresponding isolated nuclei. We further examine Mie scattering and phase‐wrapping as potential sources of error in these measurements, finding they have minimal impact. Finally, we use simulation to examine the effects of incorrect RI assumptions on nuclear morphology measurements using angle‐resolved scattering information. Despite an erroneous assumption of the nuclear refractive index, accurate measurement of nuclear morphology was maintained, suggesting that light scattering modalities remain effective. Abstract : Recent studies using quantitative phase microscopy have suggested that the nuclear refractive index is lower than that of cytoplasm. In this paper, we verify this claim in new cell lines, including non‐cancerous and primary lines. We further validate against potential corrupting factors, and examine the impact that a low nuclear index would have on light scattering technologies.